Peningkatan Kemampuan Life Skill Warga Belajar Paket C Melalui Program Keterampilan (Studi Kasus di PKBM Kusuma Bangsa Kabupaten Pali) - Fahkriyatul Kamilah; Intan Ali Pratiwi; Shomedran Shomedran (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2023)
Education plays an important role in national development where through good education human beings will be born who are able to compete in the era of globalization with high competition in all aspects. In this era of high globalization, everyone must be able to have life skills attached to them, because life skills are an educational effort to increase the capacity and capability of every citizen. The purpose of this study was to determine the increase in the life skills of the community members learning PKBM Kusuma Bangsa. The research approach used is qualitative and case studies obtained from the results of interviews and observations. Sources of research data were obtained from PKBM heads, tutors and learning residents. The results of the study show that there is a skills program provided to residents learning through handicrafts from bamboo and rattan, which is currently running well and is successful as evidenced by the increase in new skills and knowledge for residents learning package C where graduates have also been able to get jobs and businesses alone.